ANALISIS DU PONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PADA PT. PEGADAIAN (PERSERO) KANWIL II PEKANBARU - Silviana Savitri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Financial performance appraisal is a very important activity for the company. This study aims to determine and analyze the financial performance of PT. Pegadaian (Persero) Pekanbaru Regional Office II was measured using the Du Pont System method for the period 2015 to 2019 which involved the activity ratio with the profitability ratio. The type of research used in the form of secondary data which is data from financial statements. The data collection technique used is the method of documentation and interviews. The data analysis technique used is to calculate the ratios, namely Total Asset Turnover (TATO), Net Profit Margin (NPM), Return On Investment (ROI), Return On Equity (ROE) and Equity Multiplier (EM). The results of the discussion show that the performance of PT. Pegadaian (Persero) Regional Office II Pekanbaru fluctuated. This can be seen from the fluctuating state of return on equity over a five-year period. This fluctuating return on equity is influenced by fluctuations in return on investment, some of which are caused by an increase in revenue and total assets of the company but the rate of increase in company assets is greater than income, so that total asset turnover fluctuates. Even so, the net profit margin has increased even though total assets have fluctuated. Keywords: Financial Performance, Du Pont System